Implementation Of Additive Chemistry E-Modules Using the Discovery Learning Model on Student Learning Outcomes on Food Coloring Materials - Hisar Marulitua Manurung; Suprapto Manurung (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of the implementation of additive chemistry e-modules using the discovery learning model on student learning outcomes on food coloring materials. This type of research is experimental research. The experimental class was taught with the additive chemistry e-module using the discovery learning model while the control class was taught with the additive chemistry e-module without using the discovery learning model of each class on natural coloring materials in food. The instrument used was a written test in the form of multiple choice to measure student learning outcomes that have been tested instrument validation first. After being treated using the additive chemistry e-module using the discovery learning model, the calculated mean and standard deviation were 14.44 and 2.37, respectively. However, with the treatment using the additive chemistry e-module without using the discovery learning model, the mean and standard deviation were 11.94 and 2.27, respectively. Furthermore, a one-party test with a significance level of 5% was obtained tcount = 4.54 and ttable = 1.983. So it was concluded that there is a significant effect of student learning outcomes with additive chemistry e-modules using the discovery learning model